Polysocial risk factors and trajectories of antenatal moderate-to-severe depressive symptoms: a retrospective cohort study in Shenzhen, China - Jintao Xiong; Yan Yu; Xuemei Qin; Yilin Peng; Zhuo Peng; Junzhe Cheng; Weiguo Mao; Yan Wang; Yin Guo; Huiqin Li; Mi Wang; Li Zhang; et al. (BMC Medicine)
Abstract Background Antenatal depression, especially moderate-to-severe depression, is associated with adverse maternal and infant health outcomes and is affected by multiple psychosocial factors. However, the cumulative effects of psychosocial determinants and trajectories of antenatal depression are underappreciated. This study aimed to investigate the cumulative effects of various psychosocial determinants on antenatal moderate-to-severe depressive symptoms (MSD) based on the polysocial risk score (PsRS), to identify trajectories of MSD based on group-based trajectory modeling (GBTM), and to explore the association between the PsRS and diverse trajectories. Methods A retrospective cohort study was conducted among 21,336 pregnant women in Shenzhen, China, from 2020 to 2023. Antenatal depressive symptoms were assessed by the Patient Health Questionnaire-9 (PHQ-9) across three pregnancy trimesters. The PsRS was selected and calculated by counting established social determinants from four social risk domains, including socioeconomic status, lifestyle behaviors, psychosocial factors, and living conditions. GBTM was employed to identify distinct trajectories of depressive symptoms. Multinomial logistic regression investigated the relationship between PsRS and diverse trajectories. Results Of women, 9.1% experienced at least one episode of MSD across three pregnancy trimesters. An intermediate PsRS and a high PsRS were associated with higher risks of MSD during pregnancy, with the adjusted hazard ratios being 1.99 (95% CI, 1.71–2.31) and 4.44 (95% CI, 3.81–5.17), respectively, compared with those with a low PsRS. GBTM identified five distinct trajectories of antenatal depressive symptoms: persistent MSD, resolving MSD, chronic mild, resolving mild, and no depressive symptoms. Above all trajectories, persistent MSD demonstrated the highest PSRS scores and risk gradients. Conclusions This study provides a practical basis for integrating early polysocial risk screening into routine prenatal care, enabling the timely identification and targeted support of high-risk pregnant women. These findings underscore the need for incorporating comprehensive social risk assessment into maternal health policies and intervention programs to improve mental health outcomes across pregnancy.